Comprehensive analysis of the mitochondrial genome in lichen genus Xanthoparmelia: genetic diversity, intron dynamics, and evolutionary dynamics - Bahenuer, Jinsiguli; Tumur, Anwar (Frontiers in Microbiology, 2026)
Xanthoparmelia (Vain.) Hale is one of the two hyperdiverse genera in the family Parmeliaceae, with over 500 species and a wide distribution. In this study, we sequenced, assembled, and annotated the complete mitochondrial genomes of 11 Xanthoparmelia species and conducted a comprehensive analysis to clarify their genetic characteristics and taxonomic status. All 11 mitochondrial genomes consist of circular DNA molecules, with total lengths ranging from 81,194 bp to 88,245 bp and GC contents between 30.2 and 30.8%. Although the atp9 gene plays a key role in mitochondrial energy production, no atp9 gene was detected in any of the genomes. Additionally, the core genes in the mitochondrial genomes are simplified, which may be a result of coevolution. The results revealed the presence of various dispersed repeats, simple sequence repeats (SSRs), and tandem repeats, which are mainly distributed in intergenic regions and intronic regions. Introns are considered a key factor contributing to variations in mitochondrial genome size. Frequent intron loss/gain events were observed among Xanthoparmelia species, further enhancing genome diversity. The Ka/Ks ratios of all 14 protein-coding genes (PCGs) were less than 1, indicating that these genes are under purifying selection and their sequences are evolutionarily conserved. The cob gene had the smallest genetic distance, showing high conservation, while the atp6 gene had the largest genetic distance, indicating a higher mutation rate. Phylogenetic trees of Parmeliaceae were constructed using the maximum likelihood (ML) and Bayesian inference (BI) methods based on the concatenated sequences of 14 PCGs and 2 rRNAs. A well-supported topological structure was generated, clarifying the evolutionary relationships among Xanthoparmelia species. This study enriches the mitochondrial genome data of Xanthoparmelia and lays a foundation for further understanding the genetic, evolutionary, and phylogenetic relationships of species in this genus.